Characterization of Endogenous Auxins and Gibberellins Produced by Chlorella sorokiniana TH01 under Phototrophic and Mixtrophic Cultivation Modes toward Applications in Microalgal Biorefinery and Crop Research - Thi Cam Van Do; Dang Thuan Tran; Truong Giang Le; Quang Trung Nguyen (Journal of Chemistry, 2020)
Microalgae have been reported to produce endogenous phytohormones including auxins, gibberellins, cytokinins, brassinosteroids, and abscisic acid. Methanol residual released from microalgal lipid extraction usually contains a variety of bioactive compounds including the phytohormones; however, they are poorly characterized and used for other applications. This study aimed at investigating auxin, gibberellin, and cytokinin production of C. sorokiniana TH01 under phototrophic and mixtrophic cultivations. Moreover, endogenous auxins, gibberellins, and cytokinins in methanol residual obtained from the algal lipid extraction were characterized using HPLC-ESI-MS/MS toward application for crop and biorefinery research. Data showed that endogenous indole-3-acetic acid (IAA), 3-indolepropionic acid (IPA), gibberellin A4 (GA4), and gibberellin A7 (GA7) were detected in C. sorokiniana TH01 biomass. Under the phototrophic mode, total auxin and GA levels were reduced to 0.98 and 9.65 μg/g DW under salt stress (20 g NaCl/L) from 3.59 to 24.71 μg/g DW, respectively, measured for the control. Similarly, total auxins and GAs were also decreased to 0.56 and 2.86 μg/g DW, respectively, under mixtrophic growth with 6 g glucose/L. Total auxins and GAs determined in the water algal extract were 1062.7 and 2000.1 μg/L, respectively. Treatment with higher 40% (v/v) of the algal extract triggered earlier seed germination of rice and tomato plants in 2 and 1 days, respectively. Our new findings in capability of C. sorokiniana TH01 in endogenous phytohormone production contain fundamental merits for further optimization of the algal production (i.e., cultivation modes, conditions, lipids, biomass productivity, and hormone levels) to be used for biorefinery.